ARRANGING CONTROL OVER NON-CENTRALIZED WATER SUPPLY UNDER THE RISK OF GROUNDWATER DYNAMICS DISTURBANCE IN KARST TERRITORIES - Kuzichkin, Oleg; Romanov, Roman; Dorofeev, Nikolay; Grecheneva, Anastasia; Vasilyev, Gleb (Revista Inclusiones, 2020)
Presently, the use of non-centralized water supply in remote communities is the only possible option. In this case, monitoring water quality of water supply sources is a relevant and quite complicated task, especially when there are active karst processes and difficult groundwater conditions in the area of localities. Application of analytical algoristic-type water supply models under the risk of groundwater dynamics disturbance is not efficient. Major qualitative and even qualitative changes of groundwater conditions may occur between design moments, underestimation of which in expectation-driven design models may result in serious geoecological issues. This paper studies and justifies the use of the method of arranging adaptive dynamic hydrogeological control of the area of non-centralized water supply based on the identification of key zones of geodynamic karst monitoring and use of the methods of electrical express-monitoring of water resources. Identification of key zones is based on integrated analysis of available groundwater information that describes changes in groundwater hydrodynamic conditions in time during karst forecasting. It has been justified that the development of karst-suffosion processes is accompanied by much more intense dynamic changes in local areas of geologic environment compared to its summary variation intensity. Thus, information on the occurrence of destructive groundwater processes by way of selective geodynamic monitoring may be obtained much earlier than with environmental geodynamics monitoring as a whole. Experimental hydrogeological control activities of an area of non-centralized water supply have been conducted on a locality with the active manifestation of karst processes in the area of Pooksky right bank karst in Nizhny Novgorod region.